2013
DOI: 10.1080/14697017.2013.805159
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Executive Coaching in Times of Organisational Change

Abstract: Executive coaching is often used in times of organisational change to help executives develop the psychological and behavioural skills needed to focus on reaching their work-related goals whilst simultaneously dealing with the turbulence associated with organisational change. Despite its widespread use, little research has explored the impact of executive coaching during periods of organisational change. This within-subject study used both quantitative and qualitative measures to explore the impact of executiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
116
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 67 publications
5
116
0
12
Order By: Relevance
“…They facilitate business problem-solving for their coachees and develop coachees' competence to create positive outcomes [66]. For example, middle-and senior-level managers or executives who are coachees in an executive coaching context receive help from external consultants, usually with the purpose of improving work effectiveness [8,67].…”
Section: Managerial Coaching Mentoring and Organizational Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…They facilitate business problem-solving for their coachees and develop coachees' competence to create positive outcomes [66]. For example, middle-and senior-level managers or executives who are coachees in an executive coaching context receive help from external consultants, usually with the purpose of improving work effectiveness [8,67].…”
Section: Managerial Coaching Mentoring and Organizational Commitmentmentioning
confidence: 99%
“…The academic literature reports diverse types of coaching practices, including coaching leadership [7], executive coaching [8], and peer coaching [9]. Although each coaching type has a specific purpose and different coach-coachee relationship, they hold in common the goal to help individuals, groups, or organizations improve competence and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Mary et al (2010) suggest that well-designed empirical research on EI, supplemented by research of a qualitative nature, may be useful in providing richer descriptions and a better understanding of the processes and outcomes of development interventions. This idea is echoed by Grant (2013Grant ( , 2014 and McEnrue et al (2010) who also highlight the benefits of grouping participants' experiences of the processes and outcomes of the interventions into broader meaningful themes.…”
Section: • Absence Of Essential Statistical Controls And/or a Controlmentioning
confidence: 91%
“…Executive coaching is a leadership development intervention frequently found in contemporary organizations (Sherman & Freas, 2004) that has gained considerable popularity since the 1980s (Feldman & Lankau, 2005;Grant, 2014;Stelter, 2009;Western, 2012). The International Coach Federation (ICF, 2016a) found that coaching grosses USD 2.3 billion annual business revenues worldwide, with 13,895 registered coaches.…”
Section: Introductionmentioning
confidence: 99%